Patient Knowledge, Experience and Preferences towards HIV Differentiated Care Service in Kiambu County, Kenya - Beatrice May Onyango; Joseph Wang‘ombe; Collins O. Odhiambo (International Journal of Innovative Research in Medical Science, 2021)
Background: Differentiated service delivery, a model fashioned to address the specific requirements of the continuum of HIV prevention, care and treatment for a sub-type of clients, was rolled out in Kenya in 2016. Objective: The aim of the study was to determine patient knowledge, experience and preference towards differentiated service delivery for the category of patients who had completed a year of HIV treatment and were considered to be doing well and enrolled in differentiated services in facilities implementing the model in Kiambu County. Method: The study used mixed method descriptive cross-sectional survey to identify the determinants of satisfaction among stable HIV positive patients enrolled in differentiated service delivery. In the qualitative arm, a structured questionnaire was administered to 404 participants across six health care facilities who were HIV positive male or female patients above 20 years had been enrolled in differentiated service delivery. Analysis for quantitative data was two pronged; exploratory analysis to get preliminary patterns followed by inferential statistics to analyse relationship between variables of interest. Qualitative data was collected concurrently through Focused Group Discussions (FGDs) randomly selected from the same pool of patients involved in quantitative arm. On completion, triangulation was done to identify prevailing themes in qualitative and significant values in quantitative data. Results: High levels of patient satisfaction were reported. 99% of participants reported being either satisfied (45%) or being Very satisfied (54%) n=404. Knowledge in HIV condition and treatment, Knowledge of differentiated services, waiting time, savings in time and cost as well as health care worker respect had the strongest associations to satisfaction with differentiated services. Conclusion: Patients enrolled in differentiated service are satisfied with the services offered under the model.